KARIKATUR SEBAGAI KARYA KOMUNIKASI VISUAL DALAM PENYAMPAIAN KRITIK SOSIAL - Dwi Waluyanto, Heru (Institute of Research and Community Outreach - Petra Christian University, 2000)
Caricature is one effective form of visual communications in delivering social criticisms. In good caricatures there are combined elements of intelligence%2C sharpness and critical thinking as well as expressiveness in response to public living. These social criticism are packed in humorous style. Abstract in Bahasa Indonesia : Karikatur merupakan salah satu bentuk karya komunikasi visual yang efektif dalam penyampaian pesan kritik sosial. Dalam karikatur yang baik ada perpaduan unsur-unsur kecerdasan%2C ketajaman dan ketepatan berpikir kritis serta ekspresif dalam menanggapi fenomena kehidupan masyarakat%2C kritik sosial tersebut dikemas secara humoris. caricature%2C visual communication%2C social criticism